Single-cell sequencing technologies in bladder cancer research: Applications and challenges - Lyu, Tianqi; Lin, Yuanbin; Wu, Kerong; Cao, Zhanglei; Zhang, Qian; Zheng, Jianping (Frontiers in Genetics, 2022)
Bladder cancer is among the most common malignant tumors with highly heterogeneous molecular characteristics. Despite advancements of the available therapeutic options, several bladder cancer patients exhibit unsatisfactory clinical outcomes. The lack of specific biomarkers for effective targeted therapy or immunotherapy remains a major obstacle in treating bladder cancer. The rapid development of single-cell techniques is transforming our understanding of the intra-tumoral heterogeneity, thereby providing us with a powerful high-throughput sequencing tool that can reveal tumorigenesis, progression, and invasion in bladder tumors. In this review, we summarise and discuss how single-cell sequencing technologies have been applied in bladder cancer research, to advance our collective knowledge on the heterogeneity of bladder tumor cells, as well as to discern the complex ecosystem of the tumor microenvironment. The application of single-cell approaches is also uncovering the therapeutic resistance mechanism in bladder cancer, and facilitating the detection of urinary-exfoliated tumor cells. Moreover, benefiting from the powerful technical advantages of single cell techniques, several key therapeutic targets and prognostic models of bladder cancer have been identified. It is hoped that this paper can provide novel insights into the precision medicine of bladder cancer.